Hitchcock's America - Freedman, Jonathan, 1954-; Millington, Richard H., 1953- (OUP E-Books., 1999)
Alfred Hitchcock has long been understood as an inspired technician and master of abnormal psychology. The authors of this volume suggest, through readings of his American films, that he is also a cultural critic of remarkable insight and undeniable presence.